Spirituality and Work Culture in Supporting Teacher Productivity: Spiritualitas dan Budaya Kerja dalam Mendukung Produktivitas Guru - Maharani, Okvi; Hariyanto, Didik (Adabiyah: Jurnal Pendidikan Islam, 2025)
General Background: Teacher productivity is a critical factor in achieving educational quality in Islamic-based schools. Specific Background: Spiritual values and organizational work culture are frequently highlighted as contributing elements to improve teacher motivation and performance, yet studies examining both aspects simultaneously remain limited. Knowledge Gap: Previous research has focused more on technical competencies and management systems, while the integration of spirituality and work culture into teacher productivity has not been fully explored. Aim: This study aims to analyze the role of spirituality and work culture in supporting teacher productivity in Islamic-based schools. Results: The findings show that spirituality fosters commitment, responsibility, and sincerity, while a strong work culture creates discipline, collaboration, and consistency, both of which significantly reinforce teacher productivity. Novelty: The research highlights the simultaneous contribution of spiritual values and work culture, providing a more holistic perspective on teacher performance in Islamic-based schools. Implications: The results suggest that Islamic schools should prioritize both spiritual development and a supportive work culture to sustainably increase teacher productivity and institutional quality. Highlights: Spirituality builds sincerity and responsibility Work culture strengthens discipline and collaboration Both aspects improve teacher productivity holistically Keywords: Spirituality, Work Culture, Teacher Productivity, Islamic Schools, Education